Variação na concordância verbal de primeira e terceira pessoa do plural na comunidade rural afro-brasileira Mussuca – Laranjeiras/Sergipe: uma análise sociolinguística - Macêdo, Juliete Bastos (2022)
The work presented here is inserted in the area of Variationist Sociolinguistics and is linked to the research line "Variation and Change in Portuguese", of the Graduate Program in Linguistic Studies (PPGEL/UEFS). We were able to analyze the data regarding the variable use of verbal agreement in the speech of residents of the Afro-Brazilian community of Mussuca, in the municipality of Laranjeiras-SERGIPE (SE). To achieve this end, private sociolinguistic interviews and interviews in public spaces on YouTube were analyzed, seeking, from the analysis of the results, obtained through the computational program R (R CORE TEAM, 2021), to analyze whether community residents apply the standard rule in greater frequency of use, investigating whether the community moves towards the results presented in some studies on verbal agreement (LEMLE; NARO, 1977; GUY 1981; GRACIOSA, 1991; NARO; SCHERRE, 1991; RODRIGUES, 1992; SCHERRE; NARO, 1998; MONGUILHOTT, 2001; SILVA, 2003; BORTONI-RICARDO, 2008, among others). This study had as the dean hypothesis the premise that, while in the urban varieties cultured it is observed that the younger speakers tend not to mark the standard agreement, in the afro-Brazilian rural popular varieties, there is a tendency to mark the standard rule of agreement precisely among the participants of this age group (ARAÚJO, 2014). Therefore, we present a study describing the results found associated with previous studies with the objective of producing data that support the discussion, with regard to the variation of verbal agreement in a quilombola community. The results of the research confirm that the rule of verbal agreement in Portuguese brazilian system is variable. This study demonstrates that the social profile of the participant tends to influence the results of applicability of the standard rule. The internal conditioners are confirmed according to previous studies, regarding the sociocultural variables, the results are opposed to the main CV studies, because the social profile of the participant conditions the results found in this community in question. We conclude that CV in the analyzed community is a phenomenon that is in stable variation, but that if there is change the conditioners will be the same as those pointed out in the literature.